Managing teaching approach in early childhood care education towards skill development in Nigeria - Abdullahi, Nimota Jibola Kadir (Southeast Asia Early Childhood Journal, 2020)
This study embarked on managing teaching approach in early childhood care education towards skill development in Nigeria. This study determined the relationship between learner-centered approach, active learning, higher-order thinking and skill development of early childhood care education learners in North-central zone, Nigeria. Quantitative research designed was used for this study. Stratified random sampling technique was used to select 338 head teachers and 361 teachers making a total number of 699 participants in public primary school with early childhood care education centre. Data was collected using Managing Teaching Approach in Early Childhood Care Education and Skill Development Questionnaire (MTAECCESDQ). Pearson product moment correlation coefficient and linear regression analysis were used to analyze the data collected. The findings show that learner-centered approach, active learning and higher-order thinking were positively and significantly correlated with skill development. Therefore, it was recommended that head teacher should continue to encourage the teachers to make use of learner-centered approach so as to improve learners’ retention of knowledge and promote personalized learning and development. Also, head teachers and teachers should continue to inspire learners to participate in active learning in order to improve their critical thinking. Furthermore, the teachers should continue to guide learners to develop effective higher-order thinking so as to develop flexibility in thinking and reasoning skills to achieve early childhood care educational goals and objectives in Nigeria.